2012
DOI: 10.1128/jvi.01079-12
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Envelope Glycoprotein Fitness Defines Virus Population Composition following Transmission to a New Host

Abstract: Genetic variability is a hallmark of RNA virus populations. However, transmission to a new host often results in a marked decrease in population diversity. This genetic bottlenecking is observed during hepatitis C virus (HCV) transmission and can arise via a selective sweep or through the founder effect. To model HCV transmission, we utilized chimeric SCID/Alb-uPA mice with transplanted human hepatocytes and infected them with a human serum HCV inoculum. E1E2 glycoprotein gene sequences in the donor inoculum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 67 publications
2
36
0
Order By: Relevance
“…Genetic and phenotypic signatures associated with the transmission of true T/F E1E2 obtained by SGA were investigated, to the best of our knowledge, only in the previously cited study on experimental transmission of HCV in a chimeric mouse model (13). This study showed that the transmitted variants harbored key substitutions in E1E2, outside HVR1.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Genetic and phenotypic signatures associated with the transmission of true T/F E1E2 obtained by SGA were investigated, to the best of our knowledge, only in the previously cited study on experimental transmission of HCV in a chimeric mouse model (13). This study showed that the transmitted variants harbored key substitutions in E1E2, outside HVR1.…”
Section: Discussionmentioning
confidence: 97%
“…It remains unclear whether the transmission of T/F viruses results from a founder effect, with one or a small number of variants being transferred between hosts, or whether it is due to early evolutionary events, with larger numbers of variants undergoing a selective sweep due to differences in fitness constraints (10). In a recent report of the experimental transmission of HCV to chimeric SCID/Alb-uPA mice with transplanted human hepatocytes, the occurrence of selective sweeps was put forward to explain the finding that undetectable inoculum variants bearing an advantageous E1E2 motif became the major variants circulating in the infected mice (13). However, the presumed small inoculum resulting from needlestick accidents and the different proportions of T/F E1E2 sequences present in donor virus populations complicate the transposition of previously described scenarios to each of our transmission pairs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations